Differences in business fraud between state-owned and private companies: Case of Croatia - Marijana Bartulović; Dijana Perkušić; Ivan Kovačević (Financial Internet Quarterly, 2023)
Fraud presents a serious problem and arising issue for all of society at national and global levels. According to global fraud research conducted by the Association of Certified Fraud Examiners, it is estimated that the average company loses about 5% of its annual revenue due to different types of business fraud. Total estimated annual fraud losses according to global ACFE research reaches about 4.7 trillion dollars. Business frauds also present an important issue for the Croatian economy, business community and society as a whole. The main purpose of this paper is to examine differences in fraud characteristics between state-owned and private companies in the Republic of Croatia. Research was based on data on business frauds obtained by the Association of Certified Fraud Examiners Croatia which included 124 respondents. Data were related to frauds that occurred in Croatian companies in 2021 and 2020. Research results revealed how differences in fraud characteristics among privately and state-owned companies exist. Based on a sample of Croatian companies that were victims of fraud, it is noted how fraud in state-owned companies lasts longer and creates greater loses in comparison to fraud in private owned companies. Moreover, data related to estimated fraud loss and fraud duration were statistically significant in terms of differentiating these two groups of companies. Based on data on discriminatory variables a logistic regression model correctly classified 78.46% of companies in the group of companies that are privately or state-owned.
Keywords: M41; K42; 330; Frauds; State-owned Companies; Private Companies